2008
DOI: 10.1002/ange.200705643
|View full text |Cite|
|
Sign up to set email alerts
|

Asymmetric Direct Amide Synthesis by Kinetic Amine Resolution: A Chiral Bifunctional Aminoboronic Acid Catalyzed Reaction between a Racemic Amine and an Achiral Carboxylic Acid

Abstract: The formation of amide bonds by direct reaction of amines with carboxylic acids by thermal [1, 2] or catalytic methods [2][3][4][5] is generally a high temperature process. There have been no reports to date of any reactions that involve asymmetric induction during direct amide formation, with the exception of an enzyme-catalyzed process.[6] Lower temperatures are often preferred for any reaction as it can reduce the amount of reagent, reactant, or thermal product degradation. A more important consideration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…[2] In fact, a study carried out in 1999 showed that about 25 % of known pharmaceuticals contained at least one amide bond. [5][6][7][8] In particular, Hall and co-workers found that using ortho-halophenyl boronic acids as catalysts, the coupling reactions can be carried out at room temperature. The significance and limitations of catalytic approaches to amide bond formation [4a] and to condensations in general [4b] have been recently discussed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[2] In fact, a study carried out in 1999 showed that about 25 % of known pharmaceuticals contained at least one amide bond. [5][6][7][8] In particular, Hall and co-workers found that using ortho-halophenyl boronic acids as catalysts, the coupling reactions can be carried out at room temperature. The significance and limitations of catalytic approaches to amide bond formation [4a] and to condensations in general [4b] have been recently discussed.…”
mentioning
confidence: 99%
“…[5][6][7][8] In particular, Hall and co-workers found that using ortho-halophenyl boronic acids as catalysts, the coupling reactions can be carried out at room temperature. [5][6][7][8] In particular, Hall and co-workers found that using ortho-halophenyl boronic acids as catalysts, the coupling reactions can be carried out at room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…reported the use of thiourea catalyst 74 combined with DMAP as cocatalyst which allowed various primary benzylic amines to be resolved with selectivity factors of up to 24 through benzoylation with benzoic anhydride (Scheme ) 208. In addition, the KR of primary amines based on N ‐acylation with a carboxylic acid such as benzoic acid was developed by Whiting et al 209. This reaction was catalyzed by a chiral bifunctional aminoboronic acid in fluorobenzene, leading to the corresponding amides in low to moderate enantioselectivities (≤41% ee ).…”
Section: Kinetic Resolution Of Aminesmentioning
confidence: 99%
“…The use of Lewis acids as catalysts for direct amidation is usually related to boron- and transition-metal-containing compounds. 40 41 42 43 44 45 Group IV metal complexes are well represented in the latter category, 46–50 and their hydrolytic instability typically requires the use of water scavenging techniques such as azeotropic distillation to prevent deactivation of the metal catalyst by the water formed in the dehydrative reaction. For protocols carried out at temperatures below ca.…”
mentioning
confidence: 99%